Valor prognóstico da expressão de HMGB1 e IL-33 em câncer de mama triplo negativo - Sales, Francisca Janice Lopes (2023)
Breast Cancer is one of the most frequent neoplasms worldwide, contributing to female morbidity and mortality. Triple Negative Breast Cancer (CMTN) is a highly aggressive subtype of cancer that is negative for estrogen and progesterone receptors and lacks overexpression of human epidermal growth factor type 2 (C-erbB2, HER2/neu). High Mobility Group 1 (HMGB1) is a DAMP (Damage Associated Molecular Pattern) that regulates tumorigenesis, proliferation, and malignant metastasis. IL-33, a cytokine related to cell damage, has been shown to play a role in tumorigenesis and tumor-associated inflammatory responses. This study aimed to analyze the expression of HMGB1 and IL-33 as prognostic factors for CMTN. Clinical-pathological data of 122 patients diagnosed with CMTN treated at Hospital Haroldo Juaçaba were evaluated. Additionally, a Tissue Microarray (TMA) block was constructed containing samples of paraffin blocks from the biopsies of 43 patients. Then, immunofluorescence for HMGB1 was performed to quantify the intensity of expression and the percentage of fluorescent cells with cytoplasmic (cHMGB1) staining. Immunohistochemistry for HMGB1 and IL-33 was performed using the Envision DAKO® Kit detection method. In the statistical analysis, significance was considered at p<0.05 using the statistical program SPSS v.17 and GraphPad Prism v.8. Analysis of clinicopathological data indicated that patients were over 40 years old (79%) and were diagnosed with grade 2-3 ductal carcinomas (96.3%). Tumor metastasis was observed in 1.9% of cases. 66.7% of patients with CMTN who underwent adjuvant chemotherapy had low expression of HMGB1 (p<0.05). Furthermore, it was found that of patients who relapsed, 77.8% of these had low cytoplasmic expression of HMGB1 compared to high expression (p<0.05). Overall survival was similar between patients with low versus high cytoplasmic HMGB1 expression (P=0.155). For IL-33, no significant results were found. However, we emphasize that the comparative graph between High and Low expression of IL-33 versus relapse showed that 19% of patients with IL-33 High expression had a disease relapse (p>0, 05). Thus, cytoplasmic HMGB1 expression was associated with relapse and adjuvant chemotherapy in CMTN patients.